Mikroenkapsulasi Microencapsulation of Red Dragon Fruit Peel Extract (Hylocereus polyrhizus) by Microwave Assisted Foam Mat Drying Method: Study of Type and Concentration of: Mikroenkapsulasi Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) dengan Metode Microwave Assisted Foam Mat Drying: Kajian Jenis Dan Konsentrasi - Sudarminto Setyo Yuwono; Hidajatullah, Irbah Hana; Elok Waziiroh (Jurnal Pangan dan Agroindustri, 2026)
Betacyanin found in dragon fruit skin can be used as a natural dye, but it is unstable to external factors. Microencapsulation is a method used to increase the stability of betacyanin pigments during storage. This study aims to determine the effects of the type and concentration of the foaming agent on the physicochemical characteristics of microencapsulation. The study used a Factorial Randomized Block Design (RBD) with two factors. The first factor is the type of foaming agent (egg white and HPMC), and the second factor is the concentration of the foaming agents (2%, 4%, and 6%). The results of the observations were analyzed using ANOVA, followed by the Tukey test. Based on the study results, the best treatment from the Zeleny method was observed for the egg white foaming type at a concentration of 2%. Water content 4.02%, yield 17.26%, total betacyanin 41.69 mg/L, light stability 88.76%, solubility 81.1%, encapsulation efficiency 56.25%, and yellowness 9.29. This research can provide information on the use of foaming agents, their types and concentrations, and the best treatment.   Abstrak Betasianin yang terdapat di kulit buah naga dapat dimanfaatkan sebagai pewarna alami namun, tidak stabil terhadap faktor eksternal. Mikroenkapsulasi merupakan metode yang digunakan untuk meningkatkan tingkat kestabilan pigmen betasianin selama penyimpanan. Penelitian ini bertujuan untuk mengetahui pengaruh jenis pembusa dan konsentrasi pembusa terhadap karakteristik fisikokimia mikroenkapsulasi. Penelitian menggunakan Rancangan Acak Kelompok (RAK) Faktorial dengan dua faktor. Faktor pertama jenis pembusa yaitu putih telur dan HPMC dan factor kedua konsentrasi pembusa 2%,4%, dan 6%. Hasil Pengamatan dianalisis dengan ANOVA dan dilanjutkan uji Tukey. Berdasarkan hasil penelitian didapatkan perlakuan terbaik dari metode Zeleny yaitu pada perlakuan jenis pembusa putih telur dengan konsentrasi 2%. Kadar air 4,02%, rendemen 17,26%, total betasianin 41,69 mg/L, stabilitas cahaya 88,76%, kelarutan